endassign34

course Phy 201

Tʲ|Mݏassignment #034

kl{׃|S

Physics I

11-21-2008

......!!!!!!!!...................................

20:29:11

Query Class Notes #33 Why do we say that a pendulum obeys a linear restoring force law F = - k x for x small compared to pendulum length?

......!!!!!!!!...................................

RESPONSE -->

I really not for sure. Its somehing to do with The horizontal component is = to the restoring force which is = to m*g*`theta for small angles. And we have `theta which is = to x/l so we have m*g(x/l) which would be = to F=(m*g/L)x. Something like that

.................................................

......!!!!!!!!...................................

20:32:02

** The vertical component of the tension in the string is equal to the weight m * g of the pendulum. At angle `theta from equilibrium we have T cos(`theta) = m * g so T = m * g / cos(`theta).

The horizontal component of the tension is the restoring force. This component is T sin(`theta) = m * g * sin(`theta) / cos(`theta) = m * g * tan(`theta).

For small angles tan(`theta) is very close to `theta, assuming `theta to be in radians.

Thus the horizontal component is very close to m * g * `theta.

The displacement of the pendulum is L * sin(`theta), where L is pendulum length. Since for small angles sin(`theta) is very close to `theta, we have for small displacements x = displacement = L * `theta.

Thus for small displacements (which implies small angles) we have to very good approximation:

displacement = x = L `theta so that `theta = x / L, and

restoring force = m * g * `theta = m * g * x / L = ( m*g/L) * x. **

......!!!!!!!!...................................

RESPONSE -->

ok

.................................................

......!!!!!!!!...................................

21:09:45

What does simple harmonic motion have to do with a linear restoring force of the form F = - k x?

......!!!!!!!!...................................

RESPONSE -->

Not for sure

.................................................

......!!!!!!!!...................................

21:11:04

** the essential relationship is F = - k x; doesn't matter if it's a pendulum, a mass on an ideal spring, or any other system where net force is a negative constant multiple of the displacement from equilibrium.

F = m * a = m * x'', so F = - k x means that m * x'' = - k x.

The only functions whose second derivatives are constant negative multiples of the functions themselves are the sine and cosine functions.

We conclude that x = A sin(`omega t) + B cos(`omega t), where `omega = `sqrt(k/m).

For appropriate C and `phi, easily found by trigonometric identities, A sin(`omega t) + B cos(`omega t) = C sin(`omega t + `phi), showing that SHM can be modeled by a point moving around a reference circle of appropriate radius C, starting at position `phi when t = 0. **

......!!!!!!!!...................................

RESPONSE -->

What is the x' ' and is the omega=sqrt(k/m) what you are looking for in this problem

Those are details you don't need for your course. They are calculus-based and I should have noted this in the explanation.

.................................................

......!!!!!!!!...................................

21:12:46

For a simple harmonic oscillator of mass m subject to linear net restoring force F = - kx, what is the angular velocity `omega of the point on the reference circle?

......!!!!!!!!...................................

RESPONSE -->

The equation omega=sqrt(k/m)

.................................................

......!!!!!!!!...................................

21:14:20

STUDENT RESPONSE: omega= sqrt (k/m)

INSTRUCTOR COMMENT: Good. Remember that this is a very frequently used relationship for SHM, appearing in one way on another in a wide variety of problems.

......!!!!!!!!...................................

RESPONSE -->

ok

.................................................

......!!!!!!!!...................................

21:26:46

If the angular position of the point on the reference circle is given at clock time t by `theta = `omega * t, then what is the x coordinate of that point at clock time t?

......!!!!!!!!...................................

RESPONSE -->

x=radius*cos(omega*t)

.................................................

......!!!!!!!!...................................

21:26:56

since theta=omega t, if we know t we find that x = radius * cos(theta) or more specifically in terms of t

x = radius*cos(omega*t)

......!!!!!!!!...................................

RESPONSE -->

ok

.................................................

......!!!!!!!!...................................

21:39:57

Query introductory problem set 9, #'s 1-11 If we know the restoring force constant, how do we find the work required to displace the oscillator from its equilibrium position to distance x = A from that position? How could we use this work to determine the velocity of the object at its equilibrium position, provided we know its mass?

......!!!!!!!!...................................

RESPONSE -->

Im still confused about all this SHM but I think we take the the part of KE=.5 m v^2=.5 K A^2 and we solve for v which is v=sqrt(K/m)*A

.................................................

......!!!!!!!!...................................

21:40:44

** You can use the work 1/2 k A^2 and the fact that the force is conservative to conclude that the max PE of the system is 1/2 k A^2. This PE will have transformed completely into KE at the equilibrium point so that at the equilibrium point KE = .5 m v^2 = .5 k A^2. We easily solve for v, obtaining

v = `sqrt(k/m) * A. **

STUDENT COMMENT: I'm a little confused by that 1/2 k A^2.

INSTRUCTOR RESPONSE:

That is the PE at x = A. To directly reason out the expression PE = .5 k A^2 we proceed as follows:

PE = work done by system in moving from equilibirum * displacement = fAve * `ds.

The force exerted on the system at position x = A is -k A. The force exerted at position x = 0 is 0. Force changes linearly with position. So the average force exerted on the system is

( 0 - kA) / 2 = -1/2 k A.

The force exerted by the system is equal and opposite, so

fAve = 1/2 k A.

The displacement from x = 0 to x = A is `ds = A - 0 = A.

We therefore have

PE = fAve `ds = 1/2 k A * A = 1/2 k A^2.

This is also the area beneath the F vs. x graph between x = 0 and x = A. That region is a triangle with base A and altitude k A so its area is 1/2 base * height = 1/2 k A^2.

......!!!!!!!!...................................

RESPONSE -->

ok, I will work on some more problems in set #9

.................................................

......!!!!!!!!...................................

21:41:00

Query Add comments on any surprises or insights you experienced

......!!!!!!!!...................................

RESPONSE -->

.................................................

......!!!!!!!!...................................

21:41:03

as a result of this assignment.

......!!!!!!!!...................................

RESPONSE -->

.................................................

&#Your work looks good. See my notes. Let me know if you have any questions. &#